Role for autophagy-related markers Beclin-1 and LC3 in endometriosis - Zhiwei Kong; Tingting Yao (BMC, 2022)
Abstract Background Endometriosis is a common and challenging disease in women of childbearing age with high personal and social costs. Many molecular differences between ectopic and eutopic endometrium present difficulties in the development of new drug therapies and therapies. Autophagy is a response to stress and has recently been studied in human cancers. Two important autophagy genes, Beclin-1 and LC3, have been reported in several human cancers. However, the reports of Beclin-1 and LC3 in endometriosis are limited and controversial. Methods In this study, we investigated the expression of Beclin-1 and LC3 by Immunohistochemistry. Results We found their downregulation in endometriosis. We also found these two autophagy gene expression are negatively correlated with the stage of endometriosis. Conclusions Decreased expression of Beclin-1 and LC3 may be related to the occurrence and development of endometriosis.